Synthesis and Characterization of Nano Activated Carbon from Annatto Peels (Bixa orellana L.) Viewed from Temperature Activation and Impregnation Ratio of H3PO4 - Cucun Alep Riyanto; Muhamad Syaiful Ampri; Yohanes Martono (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
Nano activated carbon is activated carbon with nano-sized carbon particles and can be synthesized from cellulose-containing materials such as the Annatto peels. In this study, the synthesis of nano activated carbon of the Annatto peels was carried out in terms of activation temperature variations and the carbon impregnation ratio of 50% H3PO4 acid and determining the characteristics of nano activated carbon from Annatto peels (NAPAC). The activation method used is the impregnation of carbon in 50% H3PO4 with a ratio of 1: 3; 1: 4; 1: 5; 1: 6; and 1: 7 (w/w) for 24 hours and heating at 400; 500; 600; 700; and 800 °C for one hour. Nano activated carbon from Annatto peels (NAPAC) was characterized by Infrared Spectrophotometer (FTIR), X-ray Diffractometer (XRD), and Transmission Electron Microscope (TEM). The results of the study showed that the NAPAC can be synthesized from Annatto peels with activation by 50% H3PO4 at the temperature of 500°C and the impregnation ratio of 1:5 (w/w). The result of characterization using FT-IR, XRD and TEM showed that NAPAC contains a group of functions O-H, C-H, C=, C=C dan C-O/P=O with an amorphous carbon structure and the range of particles diameter at 22-36 nm